621.892.012 Results of the study on changes in the performance indicators of engines when operating in diesel and gas diesel modes: Results of the study on changes in the performance indicators of engines when operating in diesel and gas diesel modes - Утаев, Cобир (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Objective. It is a study of the influence of the use of various fuels on engine performance and the performance properties of oils. Methods. During the research, the laws of lubrication theory, methods of planning experiments and mathematical statistics, as well as methods based on existing regulatory documents were used. When processing the experimental data, processing methods were used on the Microsoft Office Excel application packages. Results. The operation of engines running on gaseous fuels compared to gasoline and diesel engines is characterized by a significant increase in oil service life. The most promising source of fuel for internal combustion engines can be gaseous fuels, however, their extremely poor motor properties should be taken into account if they are used in diesel engines. The methods used for using gaseous fuels do not require additional design changes or costs for obtaining fuel. The most optimal method in this situation may be to use it in gas-diesel mode in conjunction with the use of a pilot dose of diesel fuel. To reduce the wear rate of cylinder-piston group parts, methods of adding functional additives to motor oils are used in the diesel operating process; the introduced additives significantly increase the life of motor oils. Conclusion. For high-speed gas diesel engines, gaseous fuel can be used as a replacement for liquid diesel fuel. The advantage of gaseous fuel is the possibility of obtaining similar motor properties and a comparative improvement in performance indicators; there is a significant reduction in wear products in the oil, a reduction in soot emissions, which